Geomagnetic phenomena observed by a temporal station at Ulu-Slim, Malaysia during the storm of March 27, 2017 - Arafa-Hamed, T.; Khalil A.,; Nawawi M.,; Hassan, H.; M.H. Arifin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
A 3-axis fluxgate magnetometer was temporally setup for continuous recording during March 2017 at 3о 54’ 6” N, 101о 29’ 41” E, Ulu-Slim, Malaysia. On March 27th, a magnetic storm has been triggered by energetic solar wind emitted from a coronal hole on the sun that impacted the magnetosphere until the end of the measurement campaign on March 29th. The values measured at a sampling rate of 600 Hz are averaged to get a 1 Hz record from March 26 16:00 LT to March 29 12:00 LT. The 1 second data set is studied to deduce all magnetic phenomena captured during the magnetic storm. An overview of the complete record indicates the start of the storm and a complete absence of the typical diurnal variation of the total-field intensity on March 28. The diurnal variations are eliminated by subtracting a moving average of 100 samples from the recorded values. The residual shows a clear amplification of pulsations with the start of the storm. Pulsations enhancement are common around noon and is continuous on March 28th due to magnetotail activities during local night. Magnetospheric breathing as compression and expansion of the magnetosphere at long periods of 20 to 40 min is captured twice during the storm. An obvious occurrence of magnetotail reconnection is deduced by a sudden, steep increase of the total magnetic field with 50 nT at 01:30 LT on March 28. We conclude that the continuous recording of the magnetic field components provides very useful information about what processes are ongoing in space and how it might affect the logistics on the ground. The implementation of similar magnetometers as continuous observation stations would be of crucial benefits for Malaysia in both basic scientific and environmental aspects.